Knocked out by my nunga-nungas further, further confessions of Georgia Nicolson - Rennison, Louise frey50 (New York : HarperTempest, 2002)
The saga of fourteen-year-old Georgia Nicolson continues as she travels to Scotland on a nightmarish family vacation, confesses her anxiety over being the girlfriend of a sex god, and tests the limits of true friendship.
"Originally published in Great Britian in 2001 by Piccadilly Press"--T.p. verso.
Sequel to: On the bright side, I'm now the girlfriend of a sex god.
79929
Keywords: Interpersonal relations -- Fiction; Diaries -- Fiction; Humorous stories; England -- Fiction